1999
DOI: 10.1128/aem.65.3.1298-1303.1999
|View full text |Cite
|
Sign up to set email alerts
|

A Randomly Amplified Polymorphic DNA Marker Specific for the Bacillus cereus Group Is Diagnostic for Bacillus anthracis

Abstract: Aiming to develop a DNA marker specific for Bacillus anthracis and able to discriminate this species fromBacillus cereus, Bacillus thuringiensis, andBacillus mycoides, we applied the randomly amplified polymorphic DNA (RAPD) fingerprinting technique to a collection of 101 strains of the genus Bacillus, including 61 strains of theB. cereus group. An 838-bp RAPD marker (SG-850) specific for B. cereus, B. thuringiensis, B. anthracis, and B. mycoides was identified. This fragment included a putative (366-nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…The PCR reactions for amplification of the SG-749 fragment were performed in a 50 ll final volume with 5 ll 10x buffer, 2 mmol l )1 concentrations of each dNTP, 1AE5 mmol l )1 MgCl 2 , 0AE2 lmol l )1 concentrations of each primer, 1AE25 U of Taq polymerase, and 1 ll of template DNA. Cycling conditions were as described (Daffonchio et al 1999). Ten microlitres of each PCR product were restricted with 10 units of AluI (MBI Fermentas) and analysed by 3% agarose gel electrophoresis.…”
Section: Dna Preparation Pcr and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR reactions for amplification of the SG-749 fragment were performed in a 50 ll final volume with 5 ll 10x buffer, 2 mmol l )1 concentrations of each dNTP, 1AE5 mmol l )1 MgCl 2 , 0AE2 lmol l )1 concentrations of each primer, 1AE25 U of Taq polymerase, and 1 ll of template DNA. Cycling conditions were as described (Daffonchio et al 1999). Ten microlitres of each PCR product were restricted with 10 units of AluI (MBI Fermentas) and analysed by 3% agarose gel electrophoresis.…”
Section: Dna Preparation Pcr and Sequencingmentioning
confidence: 99%
“…The untypical borderline isolates were assembled, and for a systematic examination, their microbiological and molecular features were compared with a panel of defined strains of the B. cereus group, including B. anthracis. To find out which known molecular methods are most adequate to distinguish B. anthracis from other members of the B. cereus group, the following assays were performed: (i) PCR amplification of the B. anthracis specific Ba813 marker (Patra et al 1996;Ramisse et al 1999) and of the four loci A, C, D and E identified by suppression subtractive hybridization (Radnedge et al 2003), (ii) AluI restriction of the B. cereus-group-specific SG-749 fragment to obtain a restriction pattern specific for B. anthracis (Daffonchio et al 1999); and (iii) amplification of the eight variablenumber tandem repeat (VNTR) loci used for multiplelocus VNTR analysis (MLVA) (Keim et al 2000). The MLVA loci are thought to be essentially specific for B. anthracis, but no detailed analysis of their presence or absence in a variety of isolates has been published before.…”
Section: Introductionmentioning
confidence: 99%
“…anthracis is a highly fatal infectious agent in animals and humans and therefore its early and unambiguous diagnostic detection is essential for successful treatment and disease prevention. There have been many efforts to utilize rapid DNA-based detection methods, such as PCR [22][23][24][25][26][27][28][29][30][31][32][33], to replace time-consuming biochemical or culture-based diagnostic tests [34]. PCR-based methods can readily differentiate vaccine or fully virulent B. anthracis plasmid genotypes [22][23][24]26,35].…”
Section: Introductionmentioning
confidence: 99%
“…PCR methods developed for detection of the B. anthracis chromosome have suffered from lack of assay specificity; Ba813 [25,26,51], vrrA gene [27][28][29], gyrase B gene (gyrB) [30], SG-850 [31], the b subunit of RNA Table 1 Bacterial strains used in this study and their DNA-based assay response (manuscript in preparation)…”
Section: Introductionmentioning
confidence: 99%
“…Identi¢cation of B. cereus was done with PCR technique by the method previously described [12]. The two B. cereus-speci¢c primers used were: SG-749f (5P-ACTGGCT-AATTATGTAATG-3P) and SG-749r (5P-ATAATTATC-CATTGATTTCG-3P) [13]. The oligonucleotides were purchased from Hokkaido System Science (Sapporo, Japan).…”
Section: Pcr and Dot Blot Hybridizationmentioning
confidence: 99%